2013
DOI: 10.1175/bams-d-11-00160.1
|View full text |Cite
|
Sign up to set email alerts
|

Inside Volcanic Clouds: Remote Sensing of Ash Plumes Using Microwave Weather Radars

Abstract: Ash clouds due to volcanic eruptions can be detected in near-real time, quantitatively retrieved, and microphysically characterized by using ground-based microwave weather radars and their high-resolution spatial-temporal coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
62
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 55 publications
0
62
0
Order By: Relevance
“…Note that the Grímsvötn eruption considered in this work and observed by the X-band dual polarization radar is a Plinian style event, and it was classified as class 4 at least within a range 0-8 in terms of volcanic explosive index (Newhall and Self 1982). On the contrary, the Etna event, considered in the introductory paper by Marzano et al (2013b) and observed by the same radar system used in this work, is a Strombolian style eruption that typically implies a VEI less than 3. Retrievals of mass loading from space observations obtained from the LEO passive Special Sensor Microwave Imager/Sounder (SSMIS) are compared with those derived using ground-based radars.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Note that the Grímsvötn eruption considered in this work and observed by the X-band dual polarization radar is a Plinian style event, and it was classified as class 4 at least within a range 0-8 in terms of volcanic explosive index (Newhall and Self 1982). On the contrary, the Etna event, considered in the introductory paper by Marzano et al (2013b) and observed by the same radar system used in this work, is a Strombolian style eruption that typically implies a VEI less than 3. Retrievals of mass loading from space observations obtained from the LEO passive Special Sensor Microwave Imager/Sounder (SSMIS) are compared with those derived using ground-based radars.…”
Section: Introductionmentioning
confidence: 83%
“…Weather radars are an example of such sensors whose use is increasing as an additional tool for volcanic cloud monitoring and quantitative retrieval of ash. A comprehensive overview of recent progress in radar volcanology is given by Marzano et al (2013b). That paper summarize the basis fundamentals of the radar-driven remote sensing of explosive volcanic eruptions, showing how quantitative estimates of ash category and concentration can be nowadays accomplished with a fairly good degree of confidence within the spatial coverage of weather radars.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Use of weather radar for hail detection began in the 1950s with single-polarization techniques for analyzing echo intensity, spatial structure, and time evolution (Cook, 1958;Douglas and Hitschfeld, 1958). Mason (1971) suggested a 55 dBZ reflectivity threshold as an indicator of the presence of hail in S-band radars. A refinement of the relationship between the 45 dBZ level above the freezing layer and the occurrence of hail at the ground (Waldvogel et al, 1979) has been used by the Weather Surveillance Radar-1988 Doppler (WSR-88D) single-polarization systems.…”
Section: Introductionmentioning
confidence: 99%